MICROBIAL PROFILE OF INFECTIONS IN BURN PATIENTS (Journal of Forensic Medicine & Toxicology, 2017)
As per the data of Union health ministry of India, our country records 70 lakh burn injury cases annually of which 1.5 lakh people die every year. Burn patients have unique predisposition to different infections which are linked to impaired resistance from disruption of the skin’s mechanical integrity and generalized immune suppression. Infection causes 50% to 60% of deaths in burn patients in spite of intensive therapy with antibiotics both topically as well as intravenous. Sixty female burns victim were analyzed to make the microbial profile in burn patients from the surface wound and from internal organ (spleen). In burn surface wounds predominant organism was Pseudomonas followed by Klebsiella, Citrobacter. In the splenic tissue most common isolated organism was Klebsiella followed by Citrobacter and Pseudomonas. Proteus vulgaris was isolated only in spleenic tissue.
Keywords: Female Burn; Infection; Microorganism